Unveiling the diversity of longhorn beetles (Coleoptera, Cerambycidae) in Brazilian western Amazonia: a checklist of the Entomological Collection of the Federal University of Rondônia, Brazil - de Santana Souza, Diego; Andriolo, Aline; Sepúlveda, Tatiana Alejandra; Silveira, Maria Aurea Pinheiro De Almeida (Zootaxa, 2021)
An extensive checklist of the Cerambycidae deposited in the Entomological Collection of the Federal University of Rondônia (UNIR) is provided. The checklist includes photographs of 58 new records for the State of Rondônia, four of them representing new records for Brazil: Oncideres wappesi Martins & Galileo, 2005, Rhaphiptera boliviana Galileo & Martins, 2007, Tulcus liturus (Dillon & Dillon, 1945) and Xenofrea zischkai Galileo & Martins, 2012.